2012
DOI: 10.1182/blood.v120.21.1391.1391
|View full text |Cite
|
Sign up to set email alerts
|

NUP98-NSD1 Related Gene Expression Signature Is Strongly Associated with a Poor Prognosis in Pediatric Acute Myeloid Leukemia

Abstract: The cryptic t(5;11)(q35;p15.5) creates a fusion gene between the NUP98 and NSD1 genes. To ascertain the significance of this gene fusion, we explored its frequency, clinical impact, and gene expression pattern using DNA microarray in pediatric acute myeloid leukemia (AML) patients. NUP98-NSD1 fusion transcripts were detected in 6 (4.8%) of 124 pediatric AML patients. Supervised hierarchical clustering analyses using probe sets that were differentially expressed in these patients detected a characteristic gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 32 publications
9
29
2
1
Order By: Relevance
“…Although the gene expression pattern of patients with NPM1 mutation has been reported to be quite similar to AML patients with NUP98-NSD1 (showing higher levels of expression of HOXB2, -B3, -B6 and -D4) (Mullighan et al, 2007;Hollink et al, 2009Hollink et al, , 2011Shiba et al, 2013), NPM1 and NUP98-NSD1 were completely mutually exclusive in this and previous studies (Hollink et al, 2011;Shiba et al, 2013).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Although the gene expression pattern of patients with NPM1 mutation has been reported to be quite similar to AML patients with NUP98-NSD1 (showing higher levels of expression of HOXB2, -B3, -B6 and -D4) (Mullighan et al, 2007;Hollink et al, 2009Hollink et al, , 2011Shiba et al, 2013), NPM1 and NUP98-NSD1 were completely mutually exclusive in this and previous studies (Hollink et al, 2011;Shiba et al, 2013).…”
Section: Discussionmentioning
confidence: 43%
“…The frequencies of patients with high or low PRDM16 expression differed widely with respect to each genetic alteration, as follows: t(8;21), 4% vs. 96%, P < 0Á001; inv(16), 0% vs. 100%, P < 0Á001; KMT2A-PTD, 100% vs. 0%, P < 0Á001; NUP98-NSD1, 100% vs. 0%, P < 0Á001; and KIT, 12% vs. 88%, P = 0Á005. As PRDM16 was originally extracted from the NUP98-NSD1-related signature identified in the AML99 study (Shiba et al, 2013), it was also significantly overexpressed in all paediatric AML patients with NUP98-NSD1 in this study ( Figure S3). Patients with PRDM16 overexpression also more frequently harboured a normal karyotype [33/84 (39%) vs. 37/285 for low expression (13%), P < 0Á001].…”
Section: Resultsmentioning
confidence: 79%
“…was associated with poor prognosis in AMKL ( 20,28,29 Thus, all together, these findings suggested that NUP98-KDM5A was potentially a poor prognostic factor in pediatric AML patients.…”
Section: Discussionmentioning
confidence: 75%
“…Mutation analyses of FLT3-ITD, NRAS, KRAS, KIT, WT1, NPM1, and GATA1 17-20 and fusion gene analyses including CBFA2T3-GLIS2, NUP98-KDM5A, KMT2A-MLLT3, KMT2A-MLLT10, RBM15-MKL1, RUNX1-RUNX1T1, CBFb-MYH11, NUP98-NSD1, and FUS-ERG were performed using polymerase chain reaction (PCR)/reverse transcription-PCR followed by Sanger sequencing, as previously reported. [10][11][12]20 In this study, a complex karyotype was defined by three or more chromosome abnormalities. [21][22][23]…”
Section: Cytogenetic and Molecular Characterizationmentioning
confidence: 99%
“…NUP98/NSD1 fusion due to the cryptic t(5;11)(q35;p15) occurs in almost 20% of children with cytogenetic normal AML (Hollink et al, 2011) and is often associated with FLT3-internal tandem duplication (ITD) and a very poor outcome and salvage rate (Shiba et al, 2013). The data on HSCT in NUP98/NSD1 are very sparse but suggest a benefit of HSCT in CR1 (Shiba et al, 2013).…”
Section: Cytogeneticsmentioning
confidence: 99%